2000
DOI: 10.1080/00221300009598577
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Choice of Limb for Unimanual Reaching Movements?

Abstract: Currently, relatively little is known about what drives the choice of limb for goal-oriented reaching. Traditionally, the explanation has been tied predominately to motor dominance as manifested in handedness. This article offers data and an argument suggesting that handedness can be modified by attentional (spatial) information. Although motor dominance may be the controlling factor in the programming and execution of reaching movements at the midline and hemispace ipsilateral (same side) to the dominant limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 21 publications
5
50
0
Order By: Relevance
“…Extending the work of Scharoun et al. (2016) to include preadolescent children, findings are concurrent with the kinaesthetic hypothesis (Gabbard & Rabb, 2000), which states that preferred hand use will be limited in contralateral space, due to biomechanical constraints. As such, object proximity and efficiency constrain hand selection in preferential reaching task.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Extending the work of Scharoun et al. (2016) to include preadolescent children, findings are concurrent with the kinaesthetic hypothesis (Gabbard & Rabb, 2000), which states that preferred hand use will be limited in contralateral space, due to biomechanical constraints. As such, object proximity and efficiency constrain hand selection in preferential reaching task.…”
Section: Discussionsupporting
confidence: 62%
“…Notwithstanding differences in performance, similarities between preadolescents and young adults also emerged. Greater right‐hand selection in right space and when the handle was oriented to the right provides support for the kinaesthetic hypothesis (Gabbard & Rabb, 2000). As such, object proximity and orientation influence efficiency and thus constrain hand selection in unimanual object manipulation and role‐differentiated bimanual manipulation.…”
Section: Discussionmentioning
confidence: 67%
“…Psychophysical studies have suggested that arm selection is achieved via programming where motor dominance (handedness), spatial attentional information, and biomechanical advantage are used as major determinants (Gabbard and Helbig 2004; Gabbard and Rabb 2000). A number of reaction time studies have concluded that computations of arm selection take 350 -450 ms (Lépine et al 1989;Possami et al 2002;Rosenbaum 1980;Ulrich et al 1998;Wild-Wall et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…According to this idea, asymmetry in transfer occurs because the two arm controllers are differentially proficient for controlling different features of movement (i.e., dominant arm for controlling movement trajectory, nondominant arm for specifying final limb posture; Sainburg and Kalakanis 2000;Bagesteiro and Sainburg 2003;Wang and Sainburg 2007b), and the motor control system determines the direction of information flow depending on the compatibility between task requirements and arm proficiency. Thus, when the left arm performs a visuomotor adaptation task in a left workspace location following initial training with the right arm in a right workspace location, for example, the motor control system allows the nondominant controller to access all of the available information obtained during the right arm training, as indicated by a transfer of direction information from the right to the left arm (Wang and Sainburg 2006b), probably because the left arm is performing the task in a workspace in which the control system considers using this arm as a more affordable solution, as compared with using the right arm (Bryden & Roy, 2006;Gabbard & Helbig, 2004;Gabbard & Rabb, 2000). Such access would not be allowed if the left arm was performing the task in a workspace location shared by both arms, as observed in our previous studies (Sainburg and Wang 2002;Wang and Sainburg 2007a), because the control system would perceive using the right arm as a more viable option for controlling this type of information (i.e., trajectory control) in the given task-space.…”
Section: Discussionmentioning
confidence: 99%